Peran Kebijakan Lingkungan dalam Pengelolaan Limbah di PT Aneka Tambang Tbk dalam Mendukung Penerapan Green Business di Indonesia - Fairus Hasna; Rahayu Subekti; Rosita Candrakirana (Lembaga Pengembangan Kinerja Dosen, 2025)
The management of mining waste is a crucial aspect in maintaining the balance between the exploitation of natural resources and environmental protection. PT Aneka Tambang Tbk (Antam), as a mining company, strives to implement sustainable waste management policies to support the concept of Green Business in Indonesia. This study aims to analyze the role of national and international regulations in mining waste management and the implementation of these policies by Antam based on its 2020-2023 sustainability report. Using a normative juridical approach, this research finds that although regulations governing waste management are in place, challenges remain in their implementation, including harmonization with international standards and the effectiveness of supervision mechanisms. Therefore, strengthening regulations and enhancing transparency in waste reporting and management are necessary to ensure that the mining industry aligns with sustainability principles.